2018
DOI: 10.3389/fnmol.2018.00389
|View full text |Cite
|
Sign up to set email alerts
|

TPH2 Deficiency Influences Neuroplastic Mechanisms and Alters the Response to an Acute Stress in a Sex Specific Manner

Abstract: Dysregulations of the central serotoninergic system have been implicated in several psychopathologies, characterized by different susceptibility between males and females. We took advantage of tryptophan hydroxylase 2 (TPH2) deficient rats, lacking serotonin specifically in the brain, to investigate whether a vulnerable genotype can be associated with alterations of neuronal plasticity from the early stage of maturation of the brain until adulthood. We found a significant increase, in both gene and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 55 publications
2
29
1
Order By: Relevance
“…Tissues were homogenized, and proteins were extracted as previously described [16]. The protein concentration of each sample was assessed according to the Bradford protein assay procedure (Bio-Rad Laboratories) with albumin as the calibration standard.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
“…Tissues were homogenized, and proteins were extracted as previously described [16]. The protein concentration of each sample was assessed according to the Bradford protein assay procedure (Bio-Rad Laboratories) with albumin as the calibration standard.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
“…Adult male TPH2 +/+ and TPH2 −/− rats were exposed to acute restraint stress as previously described (Brivio et al, 2018;Calabrese et al, 2020). Briefly, rats were placed in an air-accessible apparatus for 1 h. The size of the container was similar to the size of the animal, making the rats almost immobile.…”
Section: Stress Proceduresmentioning
confidence: 99%
“…Psychiatric pathologies in humans have a multifactorial etiology with genetic and environmental factors that may interact thus inducing the manifestation of a wide range of symptoms McKinney, 1973, 1975). Among the genetic factors that can predispose to the development of psychiatric illnesses, such as depression, alterations in the serotonergic system are the most studied not only at clinical level but also in preclinical studies (Caspi et al, 2003;Calabrese et al, 2013;Brivio et al, 2018;Ottenhof et al, 2018). Interestingly, serotonergic projections innervate the paraventricular nucleus of the hypothalamus as well as the brain regions involved in the stress-induced activity of the HPA axis, including the prefrontal cortex (PFC) (Pan and Gilbert, 1992;Van de Kar et al, 2001;Herman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of symptoms mirrors important as pects of the clinical presentation of depressed patients with reduced central serotonin function (i. e., low 5-hydroxyindole ace tic acid levels in cerebrospinal fluid [13,14]). Using Tph2 − / − animals, we and others demonstrated that depletion of brain serotonin increases BDNF expression in hippocampus and prefrontal cortex [15][16][17] and that serotonin is required for the bi ological effects of electroconvulsive therapy [18]. In this study, Tph2 − / − and CTR mice were treated with CIT or TIA for 21 days.…”
Section: Discussionmentioning
confidence: 84%